Evaporation and contact line dynamics of surfactant droplets on a patterned surface - Huwaina Ahmad Zailudin (2018)
The study of the evaporation of liquid droplets on compact substrates and its pattern remains vital in important technology utilizations such as inkjet printing, surface cooling and surface coating [1]. Researches have been focusing on superhydrophobic surfaces with a contact angle about 150˚ due to their broad practical applications. However, there is still gap on understanding how the microstructures of the pattern surface correlate with the wetting behaviour and evaporation process of sessile droplet. The aim of this study is to investigate the wettability of special pattern surface decorated with micro-pyramid pillars and how the wettability property varies with various concentrations of surfactant solution. To achieve the aim of this study, five different parameters will be covered namely initial contact angle of various surfactant solutions, initial droplet wetting of surfactant solutions, side ratio of solutions, evaporation dynamics of droplets, volume rate of droplets and close view of contact line receding. In initial contact angle section, the droplet wetting shape and contact angle are observed. The relation between diameter and contact angle; and mode of which the droplet is undergoing are discussed in droplet evaporation dynamics. The detail receding of contact line is covered in the close view of contact line receding. It can be seen that when the droplet was dispensed on the substrate, it formed an octagonal shape and its contact angle for 45˚ line of sight (LS45˚) is smaller than 90˚ line of sight (LS90˚). The droplet shape varies accordingly to the surfactant. The side ratio for each droplet differs for each surfactants solution and this relates to the diameter and contact angle. As side ratio increase, diameter increases and contact angle declines. The relative contact angle and diameter changes as droplet undergoes constant contact radius (CCR), constant contact angle (CCA) or mixed mode. CCR signifies constant contact radius and decreasing contact angle, CCA indicates that contact angle remains constant and reduces contact line, and mixes mode designated for both contact angle and contact line that decreased synchronously. The overall evaporation duration for the droplet surfactants declines as surfactant in solution increases. Volume at low concentration of surfactant declined at slower rate compared to high concentration of surfactants. Lastly, the receding of the contact line is observed where it recedes in the line of sight for surfactant solutions whereas for none surfactant solution, it depins and its wetting shape changes to a circle.